(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Curcumin plays an important role in controlling the physiological mechanisms of inflammation and protein degradation. The aim of this study is to investigate the effect of curcumin in turmeric on muscle damage in athletes. The present research is a quasi-experimental study applied for 45 volunteers from different active sports which were selected as a statistical sample with relative random sampling and received the desired supplement or placebo for two weeks, and were randomly divided into three groups: Maltodextrin placebo control group, (Pla 0.1gr/Kg/day), experimental group 1: intake of curcumin turmeric (Cur 1000mg/day) one hour before the test, experimental group 2: intake of curcumin turmeric (Cur 1000mg/day) immediately after the test. Before warm-up and protocol, immediately after protocol and 24 hours after resistance training protocol which included lower body leg press and upper body chest press with 80% of 1RM, 5 cc venous blood was collected from upper arm vein using syringe, and creatine kinase (CK) and lactate dehydrogenase (LDH) indices were measured by photometric method. Eventually, the obtained results were analyzed with SPSS24 software. The mean value of CK and LDH in the second phase after taking curcumin compared to the first phase and the control group, showed a significant decrease (p 0.05). Thus, it can be concluded that curcumin contained in turmeric reduces the indicators of muscle damage (CK and LDH) in athletes.